(untitled) (Anwer Khan Modern Medical College Journal, 2019)
Systemic lupus erythematosus (SLE) is a rare complex autoimmune disease characterized by autoantibody formation against double strand DNA and antinuclear antibody (ANA), complement activation, and deposition of immune complexes in tissues and organs. In normal population only 0.03% suffer from SLE, among them 90% are female between the age of 20 to 30 yrs. SLE can involve any region of the visual system. Although ocular manifestations are not part of the classification criteria for SLE but retinal involvement is the most common intraocular lesion observed in up to one-third of SLE patients. The most common extra ocular lesion is keratoconjunctivitis sicca. Ocular manifestations are rarely reported at the time of disease onset, but are usually associated with active generalized systemic disease. Due to low frequency of SLE and only one third of them have ocular involvement, so reports about retinal vasculitis are very rare. But fortunately a case of Vasculitis retinae due to SLE was admitted in Anwer Khan Modern Medical College & Hospital on 04/12/2018 Anwer Khan Modern Medical College Journal Vol. 10, No. 2: July 2019, P 179-182